Enhanced Performance of Close‐Spaced Sublimation Processed Antimony Sulfide Solar Cells via Seed‐Mediated Growth - Wentao Wu; Bo Tang; Lei Wan; Xiaoli Mao; Haolin Wang; Guoqing Tong; Tao Chen; Ru Zhou (Advanced Science)
Abstract Antimony sulfide (Sb2S3) has attracted much attention due to its great prospect to construct highly efficient, cost‐effective, and environment‐friendly solar cells. The scalable close‐spaced sublimation (CSS) is a well‐developed physical deposition method to fabricate thin films for photovoltaics. However, the CSS‐processed absorber films typically involve small grain size with high‐density grain boundaries (GBs), resulting in severe defects‐induced charge‐carrier nonradiative recombination and further large open‐circuit voltage (VOC) losses. In this work, it is demonstrated that a chemical bath deposited‐Sb2S3 seed layer can serve as crystal nuclei and mediate the growth of large‐grained, highly compact CSS‐processed Sb2S3 films. This seed‐mediated Sb2S3 film affords reduced defect density and enhanced charge‐carrier transport, which yields an improved power conversion efficiency (PCE) of 4.78% for planar Sb2S3 solar cells. Moreover, the VOC of 0.755 V that is obtained is the highest reported thus far for vacuum‐based evaporation and sublimation processed Sb2S3 devices. This work demonstrates an effective strategy to deposit high‐quality low‐defect‐density Sb2S3 films via vacuum‐based physical methods for optoelectronic applications.